Dairi Diancam Tambang: Eksploitasi Lahan Pertanian yang Meresahkan Kehidupan - Niswatun Mufarrikhah; Eka Dewi Risqianti; Syifa Amalia Geanti Cahyani; Margaretha Rizky Christiana; Paras Cahyaning Tyas; Didi Pramono (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Dairi Diancam Tambang, a documentary film produced by Yayasan Diakonia Pelangi Kasih together with Legal Aid and Advocacy of the People of North Sumatra (Bakumsu). The purpose of this writing is to study the life of the people in the villages of Bongkaras and Longkotan whose people professed as farmers after the existence of mining which affected the destruction of agricultural land and river lanes source of citizens' irrigation. This study uses library studies and methods of descriptive analysis as well as the conflict theory of Karl Marx that the struggle of the proletarians in the defense of their rights seized by the bourgeoisie. The results of the research showed that there was a conflict between the public and PT DPM regarding land management permits in the protected forest area that became the site of the underground mines, as well as public concerns about their safety due to the presence of the mining company PT D PM that is in vulnerable areas of natural disasters such as earthquakes and floods, and the expectation of the village people that the government is more attentive to how the social conditions of the people to keep the earth awake.